Guinea : Fourth Review under the Extended Credit Facility Arrangement, and Financing Assurances Review -Press Release; Staff Report; and Statement by the Executive Director for Guinea. (IMF Staff Country Reports; Country Report ;, 2020)
This paper focuses on Guinea's Fourth Review Under the Extended Credit Facility (ECF) Arrangement, and Financing Assurances Review. While performance under the IMF-supported program remains broadly satisfactory, Guinea faces significant downside risks related to coronavirus disease 2019 pandemic. The IMF will remain closely engaged with the Guinean country authorities as the situation evolves, and as the authorities further develop their policy responses and financing needs change. The ECF arrangement supports strengthening Guinea's resilience, scaling-up growth-supporting investment and social-safety nets and promoting private sector development. Achieving the programmed basic fiscal surplus in 2020 will contribute to containing inflation and preserving debt sustainability. Mobilizing additional tax revenues and reducing electricity subsidies will create fiscal space to scale-up growth-supporting public investments and strengthen social safety nets. Implementing programmed tax revenues measures, adopting an automatic petroleum products price adjustment mechanism, and advancing the multi-year electricity tariff reform is key. A prudent borrowing strategy will support scaling-up growth-supporting public investment.